Process of effective management of the Eurasian transport system on the terms of integration - E. V. Pustynnikova (Управление)
Transformation of international relations caused by geopolitical processes significantly affects the development trends in foreign trade activities, global restructuring of goods movement channels, changes in the conditions of currency and customs regulation, lending, and investment. Ensuring stability, security and prosperity in the Eurasian region meets interests of many states, primarily Russia and China, as well as their closest partners. The implementation of the project on construction and modernization of the Eurasian transport system will not only neutralize risks in the context of international challenges, but will also contribute to the new ecosystem creation with great potential in the new realities. Harmonization and joint coordination of actions in accordance with the integration process progressive implementation to create a regional ecosystem in the international format will contribute to the creation of mutually beneficial partnership, development of sustainable long-term ties for implementing trade, scientific, production, and logistics projects. Conceptual provisions of the integration process to create a regional ecosystem will help to create sustainable conditions for economic development and increase corporate, sectoral and regional policies effectiveness. Building an international architecture of strategic partnership in the format of regional and sectoral interactions is a real and potentially successful approach to increase regional economic cooperation efficiency. The relevance of the study is also confirmed by the provisions of the project on transport and logistics and economic cooperation development until 2030 in priority strategic directions, primarily in financial, industrial-technological and transport, and logistics areas. The scientific novelty of the study lies in a comprehensive and integrated study of the role and regional cooperation potential and economic processes integration in China and Russia in the new ecosystem of the Greater Eurasian Partnership, as well as development of mutually beneficial cooperation between the states of the region in economic, political and humanitarian spheres. The scientific novelty of the study lies in the justification of the construction and implementation of a joint transport and logistics project on the terms of integration between China and Russia, which will predetermine the creation of the Greater Eurasian Partnership new ecosystem named with long-term mutually beneficial multilateral cooperation at the international level in the economic, political, and humanitarian fields.